STRATEGY OF NATIONAL SECURITY OF THE USA IN THE FIRST DECADE OF THE 21ST CENTURY: TO THE QUESTION OF "SELF-SUFFICIENT" SAFETY (International relations and international law Journal, 2016)
This article describes the national security strategy of theUnited States in 2002 and its consequences for further internationalrelationships of the US with other states on the politicalarena. Therefore, there are different opinions of politics and expertsof foreign countries and also there are minds of the expertsfrom Central Asia on the issues of the national security strategyof the US. Also, there are main points of the document on theissues of national security. Furthermore, this paper sets out significance of the document for the foreign policy of the US in thefi rst decade of the XXI century.
Keywords: national security; "self-sufficient" safety